Análise descritiva de duas traduções do romance Triste fim de Policarpo Quaresma para a língua inglesa - Novak, Pedro Henrique (2021)
This research aims atmakinga descriptive analysis of the first chapter of two translations of the book Triste fim de Policarpo Quaresma, by Lima Barreto, into the English language. The novel was first serialized in 1911 and later published in book format in 1915. Since 1977, the novel has been translated five times into English and for this study, the most chronologically distant translations of the full text were selected. The first is the translation of Robert Scott-Buccleuch, The Patriot, published in London by Rex Collings in 1978; the second is the translation of Francis K. Johnson, The Decline and Fall of Policarpo Quaresma, published by digital means, in 2014, by Kindle Editions. The development of this research is divided into two stages: initially, it sought to collect data about the author, his history, his oeuvre and the mapping of translations of his literary output for later analysis of the translations. For the first stage, data gatheringwas based on bibliographic research. The biographical data collected that will be used in the analysis of the translations were obtained mainly from researchers such as LimaBarreto's biographer Francisco de Assis Barbosa (2017), researcher Lilia M. Schwarcz (2017), literary critics Antonio Houaiss and Carmem Lúcia Negreiros (1997), in the critical edition of the novel by the Archivos collection, among others. The second stage of the research, which includes a presentation of the translators, consists of the descriptive analysis of the first chapter of the two selected translations with theoretical input that comprise Translation Studies theorists such as Itamar Even-Zohar (1990), Gideon Toury (2012), Lawrence Venuti (2002), André Lefevere (2007), José Lambert and Hendrik Van Gorp (2006). This research investigated whether there were divergent or convergent interpretations among translators, identified techniques and translation procedures, and analyzed whether the time period between the two editions caused changes of theoretical and/or ideological nature in translation decisions. In conclusion, it was found that there were convergent interpretations between the translators, however different techniques and procedures were used. Both translations proved to be more domesticated, using procedures that bring the text closer to the target culture, without however, hiding elements from the Brazilian culture.